Agroforestry for Carbon Sequestration in Tropical India - Dhyani, S.K.; Ram, A.; Newaj, R.; Handa, A.K.; Dev, I. (Springer, 2020)
Our atmosphere naturally contains CO2, CH4, N2O, water vapor, and other gases creating a natural greenhouse effect. But increased concentrations of these gases in the atmosphere have created an imbalance and have enhanced the greenhouse effect causing warming of the globe. Global warming will adversely affect hundreds of millions of people and will pose serious threats to the global food system and to rural livelihoods. Global warming is mainly the result of rising CO2 levels in the Earth’s atmosphere. CO2 concentration in the atmosphere is increasing at greater pace from decade to decade. To assure food security, adaptation, and mitigation to climate change is unavoidable. Many organizations worldwide are working for lowering CO2 concentration through various strategies like reduction in energy use, developing low- or no-carbon fuel, and CO2 sequestration by forestry/agroforestry and engineering techniques. Agroforestry has been recognized as a means to reduce CO2 emissions and enhance carbon sinks. Agroforestry systems (AFS) offer important opportunities of creating synergies between both adaptation and mitigation actions. Recent studies under various AFS in diverse ecological conditions showed that these systems increase and conserve aboveground and soil carbon stocks and also have an important role in increasing livelihood security and reducing vulnerability to climate change. The potential of agroforestry systems to accumulate C is estimated to 0.29–15.21 Mg ha−1 year−1. The carbon sequestration potential of AFS can be enhanced by stabilizing soil organic carbon through possible mechanisms including biochemical recalcitrance and physical protection and also reducing C losses. Furthermore, effectiveness of AFS to carbon sequestration depends on structure and functions of different component, environmental, and socio-economic factors. Carbon sequestration can be quantified by destructive or nondestructive methods. Implementing agroforestry on farmers’ fields for carbon sequestration will have major challenges which deserve to be addressed in an effective manner.